Examples of adverse effects after biological therapy - Hadas, Ewa; Bozek, Andrzej; Cudak, Anna; Ciuk, Aleksandra; Jarząb, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Psoriasis is one of the most common, chronic skin diseases of as yet unexplained etiopathogenesis. In the recent years it has been proven that an immunological factor plays an important role in the dermatosis onset. This has led to introduction of biological drugs to the disease treatment regimen, which include, inter alia, adalimumab and ustekinumab. New therapy has become an alternative for patients with psoriasis resistant to standard treatment methods as well as an alternative form of treatment in case of occurrence of severe adverse drug reactions after administration of standard treatment. Despite good treatment results the administration of these drugs is associated with the occurrence of adverse reactions. This article presents cases of 4 patients who have been administered biological treatment and in whom there have been observed, inter alia, the occurrence of hypersensitivity reactions in the form of acute urticaria as well as skin lesions of erythema multiforme nature or positive antinuclear antibodies titre. The symptoms experienced by the presented patients posed no direct threat to life and the benefits of the drugs’ administration had a significant therapeutic importance.